The Concept of Ukhuwah Wathoniah in the 12 Gurindam Poems by Raja Ali Haji - Mhd Halkis; Bani Sudardi (IBDA` : Jurnal Kajian Islam dan Budaya, 2022)
This study explains the values of ukhuwah wathoniah in the poem Gurindam 12 by Raja Ali Haji. Researchers used a literature review method with three steps. First the exploration of Malay cultural texts related to ukhuwah wathoniah, and data collection through the internet, libraries, and scientific dialogues with experts. The second, uncover the meanings of the essential phrases found in Gurindam 12. The third, constructs the values found. The study's results found that the values of ukhuwah wathoniah in Gurindam 12 contain fundamental values, practical operational values, and reflective meta-values. The fundamental values in building ukhuwah wathoniah are; knowledge, nobility, language, the goal is happiness and glory. In practical operational values, one can understand textual and contextual issues, issues of humanity and unity, and issues of justice and welfare. The Meta-Reflective Approach Gurindam 12 values can be reflected in building nationalism in the era of Industry 4.0. In conclusion, the values of ukhuwah wathoniah are relevant to understanding the phenomenon of the Unitary State of the Republic of Indonesia as a country. This originated from a sense of togetherness of nations in the post-colonial archipelago of the Dutch East Indies and continues to grow to achieve common goals. Cultural works reflect the creativity of generations in their time. Thus, Raja Ali Haji's Gurindam 12 complements the Language Manual, which was used as a guide in the Sumpah Pemuda (Youth Oath) of October 28, 1928, to promote Malay as the national language of Indonesia. The rise and fall of Indonesia-Malaysia relations can be understood in the context of ukhuwah wathoniah and ukhuwah Islamiah.